ANALISIS LAPORAN KEUANGAN UNTUK MENILAI KINERJAKEUANGAN DITINJAU DARI RASIO RENTABILITAS DANAKTIVITAS PADAPRIMER KOPERASI PRODUSENTAHU TEMPEINDONESIA (PRIMKOPTI) MURA KOTA LUBUKLINGGAU TAHUN 2010-2014Financial performance is one of the factors seen by som - Dheo Rimbano; Siti Masitoh (Jurnal Media Ekonomi (JURMEK), 2016)
Financial performance is one of the factors seen by someone to assess whether a company or cooperative can be said to be healthy or not healthy, that is, from financial statements managed by the company itself. Because it is an effort to guarantee the survival of a company or cooperative. The better the financial performance of a cooperative, the better the cooperative will be. The purpose of this study is to analyze financial statements to assess financial performance in terms of profitability and activity ratios on Primkopti Mura Lubuklinggau. From the results of the study obtained that: profitability ratio when referring to industry standards Primkopti Cooperative is still relatively unhealthy this is due to the large costs associated with sales and taxes that are high in that period and the lack of supervision from superiors in the preparation of financial statements. Likewise with the activity ratio when viewed from the calculation of the indicators and refers to the prevailing industry standards, there are Primkopi Mura Cooperatives that are healthy and some that are less healthy in every aspect of it. This is influenced by employee performance factors, as well as collection of accounts receivable from customers which are often eliminated by the Cooperative. Therefore the profit earned by the Cooperative is not as expected. Keywords: Financial Performance, Profitability Ratio with indicators in it and Activity ratios with indicators in it.